Analisis Frasa dalam Teks Esai pada Buku Bahasa Indonesia Kelas XII Kurikulum Merdeka - Azki Akhmad Mafaza; Diyas Bagus Firmansyah; Fadhila Ramadhani; Salahuddin Al Ayubi; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Universitas Katolik Widya Karya Malang, 2023)
The main discussion in this research article is the analysis of phrases that have a function in observing the use of the types of phrases contained in the essay text entitled